2009
DOI: 10.1111/j.1470-6431.2008.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Food allergic consumers' preferences for labelling practices: a qualitative study in a real shopping environment

Abstract: Food allergy is a chronic disease that can only be managed through avoidance of problematic proteins in the diet. Inappropriate communication about food allergens can cause stress and insecurity, which may have a negative impact on quality of life. The aim was to investigate whether information provided through current labelling practices meets the need of food allergic consumers. A total of 40 participants (20 adult food allergy suffers and 20 parents of food allergic children) were recruited from two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 32 publications
5
39
0
Order By: Relevance
“…Participants also expressed the view that the meaning of ''symbolic'' allergen labelling should be explained before food allergic consumers can optimally use them. This is in line with previous research indicating the need for clear, unambiguous and uniform symbols (Voordouw et al, 2009). Communication and education strategies about symbols and product information on packages might solve these issues.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Participants also expressed the view that the meaning of ''symbolic'' allergen labelling should be explained before food allergic consumers can optimally use them. This is in line with previous research indicating the need for clear, unambiguous and uniform symbols (Voordouw et al, 2009). Communication and education strategies about symbols and product information on packages might solve these issues.…”
Section: Discussionsupporting
confidence: 73%
“…Communication and education strategies about symbols and product information on packages might solve these issues. Previous research indicated that the ingredient list was not always understood because of the terminology used (Voordouw et al, 2009). The labels included in this study tried to address this issue by placing the lay explanation of difficult (chemical) terminology between brackets, an addition viewed positively by the participants.…”
Section: Discussionmentioning
confidence: 98%
“…The participants believed that, in the case of excesses, it would be sufficient to state on the label the amount that exceeds the safe limits, and in the case of trace amounts, only place a warning indicating the presence of the substance. In general, the participants complained about the complexity of the information, its position on the label, its format and packaging changes, amongst others (Voordoum et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…A number of possible information scenarios were developed based on previous research (Cornelisse-Vermaat and Pfaff et al, 2008;Cornelisse-Vermaat and Voordouw et al, 2008;Voordouw et al, 2009). The scenarios were identified through a combination of a stakeholder analysis of what was possible given existing and emerging possibilities regarding traceability, bar code labelling, and information delivery systems (Cornelisse-Vermaat and Pfaff et al, 2008) and ethnographic research to elicit the preferences of consumers for the type of information they required, together with their preferred method of delivery (Cornelisse-Vermaat and Voordouw et al, 2008;Voordouw et al, 2009).…”
Section: Methodsmentioning
confidence: 99%